Design and Characterization of Inulin Conjugate for Improved Intracellular and Targeted Delivery of Pyrazinoic Acid to Monocytes - Franklin Afinjuomo; Thomas G. Barclay; Ankit Parikh; Yunmei Song; Rosa Chung; Lixin Wang; Liang Liu; John D. Hayball; Nikolai Petrovsky; Sanjay Garg (MDPI AG, 2019)
The propensity of monocytes to migrate into sites of mycobacterium tuberculosis (TB) infection and then become infected themselves makes them potential targets for delivery of drugs intracellularly to the tubercle bacilli reservoir. Conventional TB drugs are less effective because of poor intracellular delivery to this bacterial sanctuary. This study highlights the potential of using semicrystalline delta inulin particles that are readily internalised by monocytes for a monocyte-based drug delivery system. Pyrazinoic acid was successfully attached covalently to the delta inulin particles via a labile linker. The formation of new conjugate and amide bond was confirmed using zeta potential, Proton Nuclear Magnetic Resonance (1HNMR) and Fourier transform infrared spectroscopy (FTIR). Scanning electron microscopy (SEM) confirmed that no significant change in size after conjugation which is an important parameter for monocyte targeting. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) were used to establish the change in thermal properties. The analysis of in-vitro release demonstrated pH-triggered drug cleavage off the delta inulin particles that followed a first-order kinetic process. The efficient targeting ability of the conjugate for RAW 264.7 monocytic cells was supported by cellular uptake studies. Overall, our finding confirmed that semicrystalline delta inulin particles (MPI) can be modified covalently with drugs and such conjugates allow intracellular drug delivery and uptake into monocytes, making this system potentially useful for the treatment of TB.